Urban monitoring of unpleasant odors with a handheld electronic nose - Góngora González, Andrés; Jaenal, Alberto; Chaves, David; González-Monroy, Javier; González-Jiménez, Antonio Javier (My University, 2019)
This work describes a real application of artificial olfaction where a handheld electronic nose was used as a validation tool for a chemical spillage in a southern town in Spain. The objective was to check if the palliative and precautionary measurements taken by the authorities were working effectively, removing the elevated values of phenol that were detected in a wide area of the municipality of Coria del R´ıo (Spain). To this end, a gas distribution map of the affected neighborhoods was built with a portable electronic nose taking into consideration the likely presence of other volatile chemicals in the area. For the latter, we trained a volatile chemical classifier with a dataset of typical urban smells that we wanted to remove from the results (e.g. traffic emissions, garbage, fresh-air), as well as with a specific air-born phenol dataset. Results demonstrated that the palliative measures were in general satisfactory, but some hot-spots were located where the intensity of phenol-like smell was still higher than desired. Advice was given to the local authorities to doublecheck these locations with analytical gas-monitoring equipment.
Keywords: Congresos y conferencias; Gases; Fenol; electronic nose; gas classification; smell map